Students' Perceptions towards Questions and Questioning Technique in English Classroom Interaction - Theresia Sri Nuryani; Sri Samiati Tarjana; Hersulastuti Hersulastuti (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This study was aimed at examining the perceptions of vocational high school students towards questions and questioning technique produced in classroom interactions. Questions play important role in classroom interaction, especially in the 21st century – in which critical thinking skills are the target of learning, beside content knowledge. Almost in every classroom, questions are used for various purposes. It might be given at the initial stage, when core activities take place, or at the end of the lesson. Therefore, it is important that teachers are skilful in questioning, know what types of questions can trigger critical thinking, are aware of whom the questions are for, how questions are used to manage classroom, etc. 98 students of a vocational high school participated in the study, responding to a questionnaire developed on the basis of the purposes of questions and the tactics for questioning. Descriptive qualitative was used as the method of study, with the help of questionnaire as the instrument for collecting data. SPSS data analysis application was used to get description of the phenomenon. The result showed that most students favored questions. It sharpened their thinking ability. It reflected also the fact that teachers were quite skilful in questioning, as items of the questionnaire targeted information on purposes and tactics of questioning. We can say that questions and questioning techniques were well-practiced. Key words: students’ perception, EFL classroom, purpose of questions, questioning technique